Story Time and Narrative Time to Generate Tension in Abu Gatiʿ - Mahmoud, Amel A (Humanities Journal of University of Zakho, 2018)
The present article scrutinizes two narrative aspects: story time (erzählte Zeit[1]) and narrative time (Erzähltzeit) in Shamran al-Yasery’s tetralogy Abu Gatiʿ [2] examining their functions in generating atmosphere of tension and suspense. Gerard Genette in Narrative Discourse (1980) clarifies that ‘story time’ points to the chronological sequence of the events and incidents in a story. While ‘narrative time’ refers to the ‘pseudo-temporal order’ of the incidents and their arrangement in the narrative.[3] Examining the narrative ‘anachronies’[4] of Abu Gatiʿ entails inspecting different sorts of discordance in the narrative structure of the scenes which are diagnosed, in the present article, in three kinds: reversion, ellipsis and inversion. Through following a close reading and a textual analysis specific scenes, events and incidents are examined and their connections to story time and narrative time are accentuated pinpointing within the process their thematic reference. While measuring forms of anachronies, selected letters and numbers are given to the addressed incidents in order to establish ample connections between them and to render the analysis lucid and comprehensible. [1] -Gérard Genette in Narrative Discourse (1980) cites the terms ‘erzählte Zeit’ and ‘Erzähltzeit’ from Gunther Muller, ‘Erzählzeit und erzählte Zeit’, Festschrift fur P. kluckhohn und Hermann Schneider,1948. Morphologische Poetik (Tubingen, 1968). [2] -Shamran al-Yasery, Abu Gatiʿ (Baghdad: Dar Babel,1989) [3]- Gerard Genette, Narrative Discourse, trans. Jane E. Lewin (Oxford: Basil Blackwell, 1980), 35. [4] -According to Genette, the word ‘anachrony’ refers to all forms of discordance between the two temporal orders of story and narrative. See Gerard Genette’s Narrative Discourse, 40.